-5(x-12)=-40

Simple and best practice solution for -5(x-12)=-40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x-12)=-40 equation:


Simplifying
-5(x + -12) = -40

Reorder the terms:
-5(-12 + x) = -40
(-12 * -5 + x * -5) = -40
(60 + -5x) = -40

Solving
60 + -5x = -40

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-60' to each side of the equation.
60 + -60 + -5x = -40 + -60

Combine like terms: 60 + -60 = 0
0 + -5x = -40 + -60
-5x = -40 + -60

Combine like terms: -40 + -60 = -100
-5x = -100

Divide each side by '-5'.
x = 20

Simplifying
x = 20

See similar equations:

| X+(X*0.2)=83636085.06 | | 21x-2=180 | | 20-2(x+5)=20 | | -2(1-3x)=-68 | | yn=x | | 5x-7x=11 | | -2(7x+9)=-11 | | X+(X*0.2)=91000000 | | 3z-8=7[z-3] | | x=0.89 | | X+15=95 | | 2(-6x+6)=96 | | X+(X*0.2)=101167200 | | 6x^2-13xy-28y^2=0 | | X+(X*0.2)=12 | | y=0.18x^3-2.16x^2+4.86x | | t+7-13=-4 | | sin(3x-30)=0.6 | | 4A-20=22 | | -6(7+X)=-42 | | 7.3+z=60 | | 10a+15b=2x | | 2x+10=-3x | | 2x+5*3=11 | | 2ln(2*x+1)-3ln(x+1)+ln(x+1)=0 | | 3x+18=3x+34 | | 2(4-5x)=7-5(x-2) | | 20+1d=30+.5d | | 4n+3m=11 | | -30=5w+5 | | 64=9u-u | | 103+5x=63 |

Equations solver categories